Analysis of Eternit Fiber Cement Slabs Anti-Graffiti Coating Testing Results - Urbonas, Mantas; Kelpšienė, Loreta (Jaunųjų mokslininkų darbai, 2017)
In the article Eternit fiber cement slab anti-graffiti coating resistance to cleaning is analysed. The test was carried out in 2 different situations: in a fixed field and an alternating field. The fibercement slabs have a top coating which is resistant to chemicals. Slabs are 20x30 cm in size. Rasant 031 and Arrow-Plan graffiti removers were used to clean graffiti paint. The graffiti paint level of clearance and changes in original slab colour were assessed during the tests. The level of clearance results were worst for the colour Daz3 paint. The highest change of original slab colour for Daz3 paint was measured. The anti‑graffiti coating is resistant to graffiti cleaners Rasant 031 and Arrow-Plan, but it would be better to find more effective cleaners to remove Daz3 colour paint.